Correction: Computational and experimental investigation of TmAgTe2 and XYZ2 compounds, a new group of thermoelectric materials identified by first-principles high-throughput screening. Issue 19 (27th April 2016) - Zhu, Hong; Hautier, Geoffroy; Aydemir, Umut; Gibbs, Zachary M.; Li, Guodong; Bajaj, Saurabh; Pöhls, Jan-Hendrik; Broberg, Danny; Chen, Wei; Jain, Anubhav; White, Mary Anne; Asta, Mark; et al.
Abstract : Correction for 'Computational and experimental investigation of TmAgTe2 and XYZ 2 compounds, a new group of thermoelectric materials identified by first-principles high-throughput screening' by Hong Zhu et al., J. Mater. Chem. C, 2015, 3, 10554–10565.